Adrenocortical carcinoma with contralateral renal metastases and tumor thrombus: A case report - Gahlawat, Sumit; Desai, Dhaval; Sharma, Umesh; Jain, Harsh; Tripathi, Mahesh Chandra; Sood, Rajeev (Indian Journal of Case Reports, 2019)
Adrenocortical carcinoma (ACC) is a rare aggressive malignancy. ACC with renal vein or inferior vena cava (IVC) thrombus is very rare. ACC with contralateral renal metastasis with renal vein thrombus has never been reported. Here we report first such case in the literature where a 40-year-old male presented with right flank pain and weight loss. Definitive reoperative diagnosis failed to be established. Intraoperatively, there was right adrenal mass with left renal vein thrombus invading its wall and extending upto IVC. Right adrenalectomy with left radical nephrectomy with thrombectomy was done. On cut specimen, there was a small mass lesion in the left kidney (upper pole). The diagnosis of ACC with left renal metastasis and renal vein tumor thrombus was confirmed by pathological and immune-histochemical examination. We faced various perioperative challenges in our case. Care must be taken in  preoperative diagnostics, intraoperative planning, and postoperative management as ACC may present with contralateral renal metastasis and tumor thrombus.